3C-SiC photocatalyst and its manufacturing method, and hydrogen production method
The 3C-SIC photocatalyst with a porous structure and controlled defect density, produced by a silicon carbonization method in an oxidizing atmosphere, addresses the low activity and cost issues of existing methods, enhancing hydrogen production efficiency.
Patent Information
- Application Number
- JP2021002924
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-12
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2041-01-12
AI Technical Summary
Existing 3C-SIC photocatalysts manufactured by silicon carbonization methods have low optical decomposition activity and high production costs, limiting their hydrogen production efficiency.
A 3C-SIC photocatalyst with a porous volume of 0.07 cm³/g or higher, laminated defect density of 6% or less, and a specific manufacturing method involving a mixture of carbon source and metal silicon heated in an oxidizing atmosphere at 1350 °C or less.
The 3C-SIC photocatalyst achieves high hydrogen production capacity and reduced manufacturing complexity, with improved efficiency due to its porous structure and controlled defect density.
Smart Images

Figure 0007623570000006 
Figure 0007623570000007 
Figure 0007623570000008
Abstract
Description
[Technical field]
[0001] This application discloses a 3C-SiC photocatalyst, a method for producing the same, and a method for producing hydrogen. [Background technology]
[0002] The technology of decomposing organic matter or water using photocatalysts is widely known. In particular, water decomposition using photocatalysts is promising as a renewable energy generation technology because it can convert solar energy into hydrogen energy, for example. Titanium oxide (TiO2) and other semiconductor materials have been widely used for this purpose, but they have a problem of low energy conversion efficiency.
[0003] One of the reasons for this is that the forbidden band width (hereafter referred to as the "band gap") of titanium oxide is relatively wide, at approximately 3.0 eV. When light is irradiated onto a semiconductor material in contact with H2O, electrons inside the semiconductor are excited from the valence band to the conduction band, generating electron-hole pairs. The electrons are transported to the surface of the semiconductor material and are transported to the H + The semiconductor material reduces the photons to generate H2 gas. On the other hand, the holes are also transported to the surface of the semiconductor material, and then oxidize H2O to generate O2 gas. At this time, in order for electrons to be excited in the semiconductor material, that is, for electron-hole pairs to be generated, it is necessary to irradiate the semiconductor material with light with energy greater than the forbidden band width. Therefore, in the case of TiO2, which has a band gap of approximately 3.0 eV, light with a wavelength of approximately 400 nm or less is absorbed and electrons are generated. However, considering the components of sunlight, if only photons of 400 nm or less are used to generate hydrogen, the energy conversion efficiency is only about 2% at most.
[0004] Therefore, the use of 3C-SiC as a photocatalyst for the purpose of water splitting has been proposed. 3C-SiC has a band gap of 2.23 eV and is capable of absorbing light of approximately 550 nm or less and generating electron-hole pairs. Furthermore, the lower end of the conduction band of 3C-SiC is H2 / H +The redox potential of SiO2 is lower than that of H2O / O2, and the upper end of the valence band is higher than the redox potential of H2O / O2. This makes this material suitable for use as a photocatalyst in water splitting.
[0005] Here, 3C-SiC has a crystal structure that is stable at low temperatures compared to other polymorphs such as 4H-SiC and 6H-SiC, so it is difficult to grow bulk single crystals by the sublimation recrystallization method, which is a method for manufacturing 4H-SiC and 6H-SiC. Therefore, when obtaining a 3C-SiC photocatalyst, it is common to grow 3C-SiC on a heterogeneous substrate using a chemical vapor deposition (CVD) method. The heterogeneous substrate used here is often silicon (Si) or a heterogeneous polymorph (4H-SiC or 6H-SiC) when manufacturing a single crystal. However, when manufacturing a 3C-SiC photocatalyst by the CVD method, there are problems in that the manufacturing process becomes complicated and the cost increases.
[0006] On the other hand, as a method for producing 3C-SiC for applications other than photocatalysis, there are known a silica-thermal carbide reduction method in which silicon dioxide (SiO2: silica) is mixed with a carbon source and heated to cause thermal reduction of silica by the carbon source to produce SiC, and a silicon carbonization method in which metal silicon is mixed with a carbon source and heated in a non-oxidizing atmosphere to directly carbonize silicon to produce SiC. The SiC obtained by these methods is mainly used for sintering ceramics. These manufacturing methods are different from the CVD method used for producing single crystal wafers, and are capable of producing powdered SiC. Among them, the silicon carbonization method disclosed in Patent Document 1 is a simpler synthesis method because it does not include the reduction reaction of silica in the silica-thermal carbide reduction method. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2-059413 Summary of the Invention [Problem to be solved by the invention]
[0008] The 3C-SiC photocatalyst powder produced by a simple manufacturing method has a problem of low photochemical water splitting activity. In fact, even if an attempt is made to split water using a 3C-SiC photocatalyst produced by the silicon carbonization method disclosed in Patent Document 1, a high hydrogen production rate cannot be obtained. [Means for solving the problem]
[0009] As one of the means for solving the above problems, the present application provides: 0.07cm 3 / g or more pore volume, 3C-SiC photocatalyst Disclose.
[0010] The 3C-SiC photocatalyst disclosed herein has a thickness of 0.10 cm 3 / g or more.
[0011] The 3C-SiC photocatalyst of the present disclosure may have a stacking fault density of 6% or less.
[0012] The 3C-SiC photocatalyst disclosed herein has a thickness of 0.5 m 2 / g or more 50m 2 / g or less.
[0013] The 3C-SiC photocatalyst of the present disclosure may have an average particle size of 0.05 μm or more and 100 μm or less.
[0014] As one of the means for solving the above problems, the present application provides: mixing a carbon source and silicon metal to obtain a mixture; and The mixture is heated under an oxidizing atmosphere to obtain a 0.07 cm 3 to obtain 3C-SiC having a pore volume of 1 / g or more; A method for producing a 3C-SiC photocatalyst, comprising: Disclose.
[0015] In the production method of the present disclosure, the temperature when the mixture is heated in an oxidizing atmosphere may be 1350° C. or higher and 1500° C. or lower.
[0016] In the manufacturing method of the present disclosure, the carbon source may be carbon black.
[0017] In the manufacturing method of the present disclosure, the carbon black may be at least one of thermal black and Ketjen black.
[0018] As one of the means for solving the above problems, the present application provides: A hydrogen production method using the 3C-SiC photocatalyst of the present disclosure, comprising: producing hydrogen by irradiating the 3C-SiC photocatalyst with light while the 3C-SiC photocatalyst is in contact with water and decomposing water; Hydrogen Production Method Disclose. Effect of the Invention
[0019] The 3C-SiC photocatalyst disclosed herein has a thickness of 0.07 cm 3 / g or more, the 3C-SiC photocatalyst has a high hydrogen generation capacity. In addition, the 3C-SiC photocatalyst of the present disclosure can be produced by using a simple and inexpensive silicon carbonization method. [Brief description of the drawings]
[0020] [Figure 1] An example of a hydrogen production device using a 3C-SiC photocatalyst is shown diagrammatically. [Diagram 2] 1 shows powder X-ray diffraction patterns of 3C-SiC photocatalysts according to examples and comparative examples. [Diagram 3] 1 shows the particle size distribution of 3C-SiC photocatalysts according to an embodiment and a comparative example. [Figure 4] 1 shows the relationship between the BET specific surface area and the hydrogen production rate of the 3C-SiC photocatalysts according to the examples and the comparative examples. [Diagram 5]1 shows the relationship between the pore volume and the hydrogen production rate of the 3C-SiC photocatalysts according to the examples and the comparative examples. [Figure 6] 1 shows the results of SEM observation of 3C-SiC photocatalysts according to an embodiment and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] 1. Photocatalyst A photocatalyst is a semiconductor solid that absorbs light. There is no clear distinction between semiconductors and insulators, but in the semiconductor field, those with a band gap of 3 eV or less are often called semiconductors, and those with a band gap of 3 eV or more are often called insulators. On the other hand, in the photocatalysis field, even if a material has a band gap of 3 eV or more, it is often called a photocatalyst if it causes a catalytic reaction by absorbing light.
[0022] 1.1 3C-SiC The photocatalyst of the present disclosure is composed of 3C-SiC. 3C-SiC is one of the crystal polymorphs of SiC. More than 200 types of crystal polymorphs have been confirmed for SiC, but generally, 3C-, 4H-, 6H-, and 15R- have a high occurrence probability. In this notation, the first number means the number of Si-C unit layers contained in one period in the stacking direction (c-axis), and C, H, and R mean the initial letters of the crystal system (C: cubic, H: hexagonal, R: rhombohedral). The occurrence probability of these crystal polymorphs of SiC varies depending on the temperature during synthesis. At approximately 2000°C or higher, the occurrence probability of 4H-, 6H-, and 15R-SiC is high, and at 1800°C or lower, the occurrence probability of 3C-SiC is high. In addition, these crystal polymorphs differ greatly not only in the crystal structure of SiC, but also in thermal stability and band gap. When using SiC as a photocatalyst, it is desirable to use 3C-SiC, considering the band structure and the size of the band gap. This is because 3C-SiC has a band gap of 2.23 eV and is capable of absorbing visible light (4H-SiC and 6H-SiC have band gaps of 3.26 eV and 3.02 eV, respectively, and therefore can only absorb ultraviolet light). Here, in the X-ray diffraction pattern of the photocatalyst of the present disclosure, only a diffraction peak derived from 3C-SiC may be confirmed, or, together with a diffraction peak derived from 3C-SiC, a diffraction peak derived from other components may be confirmed.
[0023] There are three common methods for improving the hydrogen production rate of photocatalysts: (1) improving crystallinity, (2) increasing the specific surface area, and (3) supporting a promoter. (1) aims to improve the hydrogen production rate by efficiently using electrons by reducing crystal defects such as stacking faults, lattice defects, and dislocations that serve as recombination sites for excited electrons and holes. (2) aims to improve the hydrogen production rate by taking advantage of the fact that an increase in the specific surface area increases the number of reaction sites, which increases the probability of a water splitting reaction occurring. (3) aims to improve the hydrogen production rate by supporting a precious metal (promoter) such as platinum, promoting charge transfer to the promoter and facilitating the water splitting reaction on the promoter.
[0024] According to the findings of the present inventors, the 3C-SiC photocatalyst synthesized by the silicon carbonization method disclosed in Patent Document 1 has a smaller stacking fault density than the 3C-SiC synthesized by the silica-thermal carbide reduction method, i.e., has high crystallinity, but tends to have a smaller specific surface area than the 3C-SiC powder synthesized by the silica-thermal carbide reduction method. In this regard, in order to significantly improve the hydrogen generation ability of the 3C-SiC photocatalyst obtained by the silicon carbonization method, it is considered effective to increase the specific surface area of the 3C-SiC photocatalyst. There are two possible methods for increasing the specific surface area of the photocatalyst: reducing the particle size and introducing a porous structure.
[0025] However, the inventors conducted various experiments and confirmed that there is no clear correlation between the specific surface area and hydrogen generation capacity of 3C-SiC photocatalysts. In other words, even if the specific surface area of a 3C-SiC photocatalyst is increased, the hydrogen generation capacity does not necessarily increase. On the other hand, there is a clear correlation between the pore volume and hydrogen generation capacity. In other words, in order to significantly improve the hydrogen generation capacity of a 3C-SiC photocatalyst, it is more effective to increase the pore volume of the photocatalyst than to increase the specific surface area of the photocatalyst.
[0026] 1.2 Pore volume The 3C-SiC photocatalyst disclosed herein has a thickness of 0.07 cm 3 / g or more. As described above, according to the new findings of the present inventors, for 3C-SiC photocatalysts, while there is no clear correlation between the specific surface area and hydrogen generation capacity, there is a clear correlation between the pore volume and hydrogen generation capacity. In particular, when the pore volume of the 3C-SiC photocatalyst is 0.07 cm 3 / g or more, the pore volume is 0.07 cm 3 / g, the hydrogen production capacity as a photocatalyst is significantly improved. 3 / g or more, and 3 / g or more. The inventors believe that the increase in the hydrogen generation rate due to the increase in the pore volume of the 3C-SiC photocatalyst is due to the following estimated mechanism. That is, the larger the pore volume of the 3C-SiC photocatalyst, the more likely it is that diffuse reflection of light occurs in the pores, and the more frequently the hydrogen generation reaction occurs, which is thought to improve the hydrogen generation ability of the photocatalyst. In addition, there is a certain degree of correlation between the specific surface area and the pore volume, and the larger the pore volume, the more the specific surface area tends to increase, so it is thought that the larger the pore volume, the more the reaction efficiency between excited electrons or holes and water improves, and the hydrogen generation ability of the photocatalyst improves. Furthermore, there is a possibility that the reaction sites are distributed unevenly inside the pores rather than on the particle surface, and it is thought that by increasing the pore volume, the reaction sites increase, and the hydrogen generation ability of the photocatalyst improves. The upper limit of the pore volume of the 3C-SiC photocatalyst is not particularly limited. The 3C-SiC photocatalyst of the present disclosure can be, for example, 1.00 cm 3 / g or less.
[0027] The pore volume of the 3C-SiC photocatalyst can be measured using a gas adsorption method. Specifically, a specific surface area / pore distribution measuring device (Microtrack-Bel, BELSORP MINI X) is used to perform the measurement by the constant volume method using nitrogen as the adsorbed gas. That is, a glass tube containing a sample is immersed in liquid nitrogen at -196°C, and the inside of the tube is evacuated. After that, the relative pressure (= adsorption equilibrium pressure / saturated vapor pressure) of 5.0×10 -4 Starting from 2.5×10 -3 Finally, the final value is 9.990×10 -1 The relative pressure is changed so that the amount of adsorbed nitrogen is measured. The pore distribution is calculated from the measured amount of adsorbed nitrogen and the relative pressure using the Dollimore-Heal method, which assumes that the pores are cylindrical, and the pore volume is calculated.
[0028] 1.3 Stacking fault density As described above, it is known that crystal defects (stacking faults, atomic vacancies, grain boundaries, etc.) in a photocatalyst become recombination sites of excited electrons and holes, reducing the activity of the photocatalyst. That is, the fewer the crystal defects, the more electrons and holes are likely to be used in the photocatalytic reaction. The 3C-SiC photocatalyst of the present disclosure may have a smaller stacking fault density than, for example, a 3C-SiC photocatalyst obtained by a silica carbothermal reduction method. For example, the 3C-SiC photocatalyst of the present disclosure may have a stacking fault density of 6% or less, or may have a stacking fault density of 5% or less. The smaller the stacking fault density, the better, and the lower limit is not particularly limited.
[0029] The stacking fault density of the 3C-SiC photocatalyst can be obtained from the X-ray diffraction pattern. Specifically, an X-ray diffraction pattern is obtained for the 3C-SiC photocatalyst using CuKα as a radiation source, and the ratio x between the intensity at 2θ=33.6° and the intensity at 2θ=41.4° is calculated. The stacking fault density Y (%) of the 3C-SiC photocatalyst can be calculated by substituting this x into the following formula (Journal of the Ceramic Society of Japan 99 [6] 443-447).
[0030]
number
[0031] Furthermore, when an X-ray diffraction pattern of the 3C-SiC photocatalyst disclosed herein is obtained using CuKα as a radiation source, the ratio x of the intensity at 2θ=33.6° to the intensity at 2θ=41.4° in the X-ray diffraction pattern may be 0.23 or less.
[0032] 1.4 Shape and size The shape of the 3C-SiC photocatalyst may be, but is not limited to, a lump-like bulk or a powder. In particular, when the photocatalyst is in a powder form, the specific surface area is likely to be large, the reaction substrate is increased, and the reaction efficiency of excited electrons and holes can be improved. Here, the powder refers to a solid aggregate having an average particle diameter of 1 mm or less when the particle size distribution is measured by wet laser diffraction. The 3C-SiC photocatalyst of the present disclosure may be a powder made of 3C-SiC that is pressed into a molded body. Even if the powder is pressed into a molded body, the pore volume does not change significantly.
[0033] The specific surface area and the particle size are inversely proportional to each other, and the smaller the particle size, the larger the specific surface area, which can improve the reaction efficiency. 3 The specific surface area and particle size are not particularly limited as long as the specific surface area is 0.5 m / g or more. 2 / g or more 50m 2 The specific surface area of the 3C-SiC photocatalyst may be less than 1 m / g (BET specific surface area). 2 / g or more, 5m 2 / g or more or 10m 2 / g or more, 2 / g or less, 30m 2 / g or less or 20m 2 / g or less. The 3C-SiC photocatalyst of the present disclosure may have an average particle size of 0.05 μm or more and 100 μm or less. The average particle size of the 3C-SiC photocatalyst may be 0.1 μm or more or 0.2 μm or more, and may be 50 μm or less, 10 μm or less, 5 μm or less, 1 μm or less, or 0.5 μm or less. The average particle size of the 3C-SiC photocatalyst is the particle size at 50% cumulative value (median size, D50) in the volume-based particle size distribution determined by a laser diffraction / scattering method.
[0034] 2. Photocatalyst manufacturing method The present inventors have conducted various experiments on the production of 3C-SiC photocatalysts by silicon carbonization, and have found that the pore volume of the 3C-SiC photocatalyst can be increased by synthesizing 3C-SiC by silicon carbonization using a carbon source and metallic silicon in an oxidizing atmosphere (oxygen-containing atmosphere) rather than the conventionally common non-oxidizing atmosphere. That is, the method of producing a 3C-SiC photocatalyst disclosed herein involves mixing a carbon source and metallic silicon to obtain a mixture, heating the mixture in an oxidizing atmosphere to obtain a pore volume of 0.07 cm. 3 and obtaining 3C-SiC having a pore volume of at least 1 / g.
[0035] 2.1 Carbon source The carbon source may be any source containing carbon as a main component. For example, simple carbon such as graphitic carbon or non-graphitic carbon (carbon black, glassy graphite, etc.) may be used as the carbon source. According to the findings of the present inventors, the desired silicon carbonization reaction is easily caused, particularly when carbon black is used as the carbon source. In addition, when carbon black is used, there is an advantage that it can be easily removed if it is mixed into the product without reacting.
[0036] The shape of the carbon source is not particularly limited. From the viewpoint of more efficiently carbonizing the metal silicon, the carbon source may be particulate. When the carbon source is particulate, the average particle size may be, for example, 10 nm or more or 1 μm or less. Here, the average particle size of the particles of the carbon source other than carbon black (for example, particulate graphite) is the particle size (median size) D50 at an integrated value of 50% in the volume-based particle size distribution obtained by a laser diffraction / scattering method. In addition, the average particle size of carbon black means the average diameter (average value of circle equivalent diameters) calculated by measuring the smallest spherical (having an outline due to microcrystals and being inseparable) component constituting the carbon black aggregate with an electron microscope (Carbon Black Yearbook, 60th Anniversary Issue, No. 58, 2008, Carbon Black Association, p. 82). In general, the smallest spherical particles constituting the carbon black aggregate cannot be separated and exist in a fused state.
[0037] When carbon black is used as the carbon source, it is preferable to use powdered carbon black, but powdery aggregated carbon black may be pulverized and used. Carbon black includes acetylene black, ketjen black, thermal black, etc., depending on the manufacturing method and raw materials, but the type of carbon black that can be used in this embodiment is not particularly limited. As far as the inventors have confirmed, the desired 3C-SiC photocatalyst is easily obtained, especially when the carbon black is at least one of thermal black and ketjen black.
[0038] 2.2 Silicon metal As described above, in the manufacturing method of the 3C-SiC photocatalyst of the present disclosure, 3C-SiC is produced by the silicon carbonization method. In order to cause such a reaction, metal silicon (silicon element) is used as a raw material together with the carbon source. The metal silicon may contain impurities.
[0039] The shape of the metal silicon is not particularly limited. The shape of the metal silicon can be selected according to the shape of the desired 3C-SiC. For example, in addition to particulate (powdered), it may be a single crystal, an amorphous body, or a molded body obtained by processing powder in advance by pressing or the like. When the metal silicon is particulate, the particles may be primary particles or secondary particles formed by agglomeration of primary particles. When the metal silicon is particulate, its average particle size may be, for example, 10 nm or more and 100 μm or less. The average particle size of metal silicon is the particle size at 50% cumulative value (median size, D50) in the volume-based particle size distribution obtained by a laser diffraction / scattering method.
[0040] 2.3 Mixtures In the manufacturing method of the 3C-SiC photocatalyst of the present disclosure, the carbon source and metal silicon are mixed to obtain a mixture. The mixing method is not particularly limited, and the mixture may be mixed by hand using an agate mortar or the like, or may be mixed mechanically using a mixing device such as a ball mill. The mixing time is also not particularly limited.
[0041] The mixture ratio of the carbon source and the metal silicon may be any mixture ratio capable of producing 3C-SiC. For example, the molar ratio C / Si of C and Si contained in the mixture may be 1.0 or more. In order to leave as little unnecessary carbon as possible after the silicon carbonization reaction, the molar ratio C / Si may be 3.0 or less.
[0042] 2.4 Oxidizing atmosphere In the prior art, when synthesizing SiC by silicon carbonization, the following reaction (1) is usually carried out in a non-oxidizing atmosphere (inert atmosphere). Si + C → SiC (1)
[0043] The silicon carbonization method consists of a simple reaction as shown in the above formula, but there is still no unified understanding of the reaction mechanism. Research is underway on a method for carbonizing a silicon substrate by irradiating the silicon substrate with carbon molecules (J. Appl. Phys. 74 (7) 4438-4445), and the most likely mechanism is that silicon atoms diffuse toward and dissolve into the carbon atoms incident on the silicon substrate to produce silicon carbide. A similar mechanism can also be used to generate SiC when a silicon substrate is irradiated with hydrocarbon molecules (Vacuum 14(12) 992-1000). In either case, the SiC grows almost epitaxially or heteroepitaxially with respect to the surface orientation of the silicon substrate, and it is unlikely that SiC with a pore structure can be synthesized by this method.
[0044] On the other hand, according to the new findings of the present inventor, when 3C-SiC is obtained by the silicon carbonization method under an oxidizing atmosphere containing oxygen, as in the manufacturing method of the 3C-SiC photocatalyst disclosed herein, the generated 3C-SiC has a complex shape with many projections and recesses. This is presumed to be due to the following mechanism. That is, when oxygen is present in the system, the generated SiC may be thermally oxidized, and silicon dioxide may be formed on the SiC surface, which may inhibit the growth of SiC. That is, due to the presence of oxygen, in the synthesis process of 3C-SiC, the growth of 3C-SiC is stopped on part of the surface due to oxidation, and the growth of 3C-SiC proceeds on other parts, and these are thought to be repeated. As a result, it is thought that SiC with a complex shape with many projections and recesses and a pore structure without clear facets is generated.
[0045] As described above, in the method for producing a 3C-SiC photocatalyst of the present disclosure, the above mixture is heated in an oxidizing atmosphere to form a 0.07 cm 3 The 3C-SiC has a pore volume of 0.07 cm3 / g or more. Here, the "oxidizing atmosphere" refers to an atmosphere containing oxygen. The oxygen concentration in the oxidizing atmosphere is not particularly limited, and is preferably 0.07 cm3 / g or more. 3 A concentration capable of producing 3C-SiC having a pore volume of 100 / g or more is appropriately selected. For example, the oxidizing atmosphere may be an atmosphere containing oxygen at 1 volume % or more, 2 volume % or more, 3 volume % or more, 4 volume % or more, 5 volume % or more, 6 volume % or more, or 7 volume % or more. The oxidizing atmosphere may be an atmosphere containing oxygen as well as a gas other than oxygen. For example, an air atmosphere, an atmosphere in which air or oxygen is diluted with an inert gas (e.g., nitrogen or argon), and the like can be mentioned.
[0046] 2.5 Heating The temperature at which the mixture is heated under an oxidizing atmosphere may be a temperature at which 3C-SiC can be produced. Specifically, it is known that 3C-SiC is a phase that is relatively thermally stable at about 1800°C or less compared to heterogeneous polymorphs. On the other hand, if the heating temperature is too low, the above reaction (1) does not occur, and 3C-SiC cannot be obtained. The heating temperature may be, for example, 1300°C or more, 1350°C or more, or 1400°C or more, or 1800°C or less, 1700°C or less, 1600°C or less, 1500°C or less, or 1450°C or less. According to the findings of the present inventors, when the heating temperature is 1350°C or more and 1700°C or less, particularly when the heating temperature is 1350°C or more and 1500°C or less, a desired 3C-SiC photocatalyst is easily obtained. In particular, when the heating temperature is 1400°C or more and 1450°C or less, a 3C-SiC photocatalyst having a larger pore volume is easily obtained.
[0047] The heating time is not particularly limited, and may be any time that allows the desired 3C-SiC photocatalyst to be obtained. The heating time may range from several minutes to several hours. In this case, the specific surface area of the 3C-SiC photocatalyst is 0.5 m 2 / g or more 50m 2 / g or less, and the average particle size is often 0.05 μm or more and 100 μm or less.
[0048] The reaction vessel for the silicon carbonization reaction may be, for example, a crucible-shaped vessel made of graphite or a high melting point metal, but may be any other reaction vessel as long as it is not significantly damaged at the temperature of synthesis of SiC.
[0049] In the 3C-SiC photocatalyst produced by the method of the present disclosure, unreacted metallic silicon, carbon, and silicon dioxide generated by reaction with oxygen in the atmosphere may remain. In this case, metallic silicon and silicon dioxide can be removed by contacting with, for example, fluoronitric acid (a mixture of hydrofluoric acid and nitric acid), and carbon can be removed by heat treatment in air. In other words, the method of producing the 3C-SiC photocatalyst of the present disclosure may include a post-treatment step of removing metallic silicon, silicon dioxide, and carbon remaining in the product after synthesizing 3C-SiC.
[0050] 2.6 Supplementary Information Although not based on the silicon carbonization method, there are some findings regarding the synthesis of 3C-SiC having a porous structure. For example, in JP 2014-177357 A, a silylene-acetylene compound is used as a precursor, and the precursor is fired to synthesize 3C-SiC having fine pores. However, this method is unclear as to whether 3C-SiC having the above-mentioned pore volume can be obtained, and there is also a problem that the synthesis time is long. In addition, in JP 2015-74565 A, 3C-SiC having fine pores is synthesized by mixing phenolic resin and silica aerosil and heating in an argon atmosphere. However, in this case, only a pore volume of about 0.01 cc / g at most can be obtained. In addition, this method synthesizes SiC by reducing the silica in the aerosil with the carbon atoms contained in the phenolic resin, and can be said to be a type of SiC synthesis method using a silica-thermal carbothermal reduction method. Furthermore, in JP 2010-138049 A, an intermediate porous body containing silicon carbide powder and carbon powder is produced using an aqueous slurry containing the silicon carbide powder and the carbon powder, the intermediate porous body is dried, and the dried intermediate porous body is impregnated with silicon using silicon vapor to synthesize silicon carbide. However, it is unclear whether this method can produce 3C-SiC having the above-mentioned pore volume, and it is difficult to say that this method is a simple synthesis method, since the stirring process takes 16 hours and silicon vapor and a vacuum furnace are required. The present inventor also synthesized 3C-SiC using a silicothermal carbothermal reduction method, which is a simple method compared to the above-mentioned method, but the pore volume was only 0.01 cm at most. 3 Only a pore volume of 0.01 g / g was obtained.
[0051] In contrast, according to the 3C-SiC manufacturing method disclosed herein, by introducing a small amount of oxygen when synthesizing a 3C-SiC photocatalyst using the simple silicon carbonization method, a 3C-SiC photocatalyst with high hydrogen generation capability can be obtained by increasing the pore volume.
[0052] 3. Hydrogen production method The technology of the present disclosure also has an aspect as a hydrogen production method. That is, the hydrogen production method of the present disclosure is a hydrogen production method using the 3C-SiC photocatalyst of the present disclosure, characterized in that hydrogen is produced by decomposing water by irradiating the 3C-SiC photocatalyst with light while the 3C-SiC photocatalyst is in contact with water.
[0053] The form of the photocatalyst during hydrogen production is not particularly limited. For example, a particulate photocatalyst may be dispersed in water and irradiated with light to cause a water splitting reaction to produce hydrogen, or a photocatalyst may be formed into a panel, and the panel may be immersed in water and irradiated with light to cause a water splitting reaction to produce hydrogen, or an electrode for water splitting may be formed using the photocatalyst, and the electrode may be immersed in water and irradiated with light to perform water electrolysis. The container for holding water and the photocatalyst may be any container made of a material having translucency, and examples of the container include resins such as acrylic resin and polyvinyl chloride resin, glass, natural quartz, synthetic quartz, and inorganic materials such as soda lime glass. For example, sunlight may be used as the light source. Alternatively, artificial light other than natural light may be used.
[0054] In particular, when hydrogen is produced on a large scale by a photochemical water splitting reaction, it is preferable to use the electrode for photochemical water splitting reaction from the viewpoint of promoting the water splitting reaction by applying a bias. In another embodiment, the 3C-SiC photocatalyst of the present disclosure can be used to completely split water by itself, and a laminate having a photocatalyst layer containing the photocatalyst on a substrate, or a composite containing the photocatalyst, can be placed in water without applying a bias. In this case, processing and handling are easy, maintenance is easy, and the cost of an artificial photosynthesis device that requires a large area can be reduced. In other words, an industrially advantageous water splitting device, oxygen generation device, hydrogen generation device, or artificial photosynthesis system can be obtained. EXAMPLES
[0055] The technology of the present disclosure will be explained in more detail below based on examples, but the technology of the present disclosure is not limited to these examples.
[0056] 1. Example 1 1.1 Production of 3C-SiC photocatalyst Metal silicon powder (Kojundo Kagaku Kenkyusho, SIE23PB) with an average particle size of 3 μm and thermal black (Nippon Steel Carbon, HTC#20) with an average particle size of 100 nm were weighed so that the C / Si (molar ratio) was 1.4, and were put into an agate mortar, and mixed so that the color of the powder was visually uniform to obtain a mixture. The mixture was then placed in a graphite crucible (Shin-Nihon Techno Carbon Co., Ltd., IGS-743), and the crucible was placed in a box-type muffle furnace (Motoyama, SC2025-D). Then, nitrogen was flowed into the furnace at a flow rate of 5.0 L / min or more to make the oxygen concentration in the furnace 7.0-8.0 vol%. In this state, the temperature was first raised to 500°C over 30 minutes, held at 500°C for 30 minutes, and then raised to 1400°C over 1 hour, held at 1400°C for 1 hour, and naturally cooled to room temperature to obtain a product. The product was heated in an electric furnace (Advantec, FUW220PA) at 900°C for 12 hours to remove unreacted carbon components remaining in the product. Next, hydrofluoric acid (Kishida Chemical, special grade, concentration 46%) and nitric acid (Kishida Chemical, special grade, concentration 60%) were mixed in a volume ratio of 1:1 to 1:2 to dissolve and remove the metallic silicon and silicon dioxide remaining in the product, thereby obtaining a photocatalyst powder according to Example 1.
[0057] 1.2 Phase identification by powder XRD measurement The photocatalyst powder obtained as described above was subjected to the identification of the crystal phase by the powder XRD method. Specifically, a glass plate 50 mm long and 32 mm wide with a recess 20 mm long, 20 mm wide, and 0.5 mm deep as a sample introduction part was used as a sample holder, and an X-ray diffractometer (Rigaku, fully automatic multipurpose X-ray diffractometer SmartLab) was used to perform 2θ / θ scans with CuKα as the radiation source, tube voltage 40 kV, tube current 30 mA, step width 0.01°, and scan speed 10° / min. The phase was identified by the diffraction pattern using PDF card number 01-075-0254 (3C-SiC) in the database (ICDD PDF-2).
[0058] 1.3 Measurement of pore distribution and pore volume by gas adsorption method The pore volume of the photocatalyst powder obtained as described above was measured using the gas adsorption method. Specifically, a specific surface area / pore distribution measuring device (Microtrack-Bel, BELSORP MINI X) was used to perform the measurement by the constant volume method using nitrogen as the adsorbed gas. That is, a glass tube containing the sample was immersed in liquid nitrogen at -196°C, and the inside of the tube was evacuated. After that, the relative pressure (= adsorption equilibrium pressure / saturated vapor pressure) of 5.0 x 10 -4 Starting from 2.5×10 -3 Finally, the final value is 9.990×10 -1 The relative pressure was changed to measure the amount of adsorbed nitrogen. From the measured amount of adsorbed nitrogen and the relative pressure, the pore distribution was calculated using the Dollimore-Heal method, which assumes that the pores are cylindrical, and the pore volume was obtained.
[0059] 1.4 Particle size distribution measurement using a laser diffraction particle size analyzer The particle size distribution of the photocatalyst powder obtained as described above was measured using a laser diffraction particle size distribution measurement method. Specifically, a laser diffraction particle size distribution measurement device (Malvern, MasterSizer2000) was used, water and photocatalyst powder were put into the device, the inside of the cell was stirred at a stirring speed of 3500 rpm, and ultrasonic waves were applied to thoroughly disperse the photocatalyst powder in the cell, and then the dispersion medium was water (refractive index 1.33) and the measurement target was silicon carbide (refractive index 2.6, extinction coefficient 0.1) under the measurement conditions, and the average particle size (D50) of the photocatalyst powder was calculated from the obtained particle size distribution. The average particle size of silicon carbide is the particle size (median size, D50) at 50% of the cumulative value in the number-based particle size distribution obtained by the laser diffraction / scattering method.
[0060] 1.5 Evaluation conditions for hydrogen production rate of photocatalyst powder The amount of hydrogen generated by the photocatalyst powder was measured and evaluated using the device shown in Figure 1. 10 mg of the photocatalyst powder and 10 ml of ultrapure water (>18 Ω·cm) were mixed to prepare a mixed solution 13, and the mixed solution 13 and a 10 mm stirring bar 18 were placed in a glass test tube 17 with a volume of 20 ml. A rubber stopper 15 was attached to the test tube, and a sealant 16 made of plastic paraffin film and vinyl tape was wrapped around the rubber stopper 15 and the test tube 17. Next, while stirring the mixed solution at 300 rpm using a stirrer 14, N2 gas was bubbled into the inside of the test tube and the mixed solution for 5 minutes to remove the air. The light intensity of the solar simulator 11, which is the light source, was adjusted to 1 sun using a reference solar cell (Konica Minolta, AK-200). The stirrer 14 was rotated to 1000 rpm to irradiate the test tube with simulated sunlight 12 from the solar simulator 11. Artificial sunlight was irradiated for different irradiation times of 3 hours, 6 hours, and 18 hours. Although irradiation from the side is shown in FIG. 1, irradiation from the bottom, top, or slope is also acceptable. Although the case where a solar simulator 11 is used as the light source has been described here, sunlight, an Hg lamp, an Xe lamp, or a halogen lamp may also be used. The gas components and concentration of the generated gas were analyzed by collecting 1 ml of the gas phase inside the test tube from the top of the rubber stopper with a microsyringe and using a gas chromatograph (Shimadzu, GC-2014) for which a calibration curve had been prepared in advance. The analysis results, the pressure of the gas phase (1 atm), the volume of the gas phase part of the test tube (9.056 mL), and the gas constant (R = 8.31 JK -1 Mol -1 The amount of hydrogen generated was calculated using the gas equation of state (pV = nRT) from the temperature of the gas phase (293K) and the temperature of the gas phase (293K). The hydrogen generation rate was calculated by linear fitting to the amount of hydrogen generated at each light irradiation time.
[0061] 2. Examples 2 to 4 and Comparative Examples 2 to 5 As shown in Table 1 below, the raw materials and synthesis conditions were changed, and photocatalyst powders according to Examples 2 to 4 and Comparative Examples 2 to 5 were obtained in the same manner as in Example 1, and various evaluations were carried out. Note that Ketjen Black was ECP600JD from Lion Specialty Chemicals, and Acetylene Black was Li-400 from Denka. The rest was the same as in Example 1.
[0062] 3. Comparative Example 1 Metallic silicon powder (Kojundo Chemical Laboratory, SIE23PB) with an average particle size of 3 μm and thermal black (Nippon Steel Carbon, HTC#20) with an average particle size of 100 nm were weighed out so that the C / Si (molar ratio) was 1.4, and placed in an agate mortar and mixed until the powder color was visually uniform. The mixed powder was then placed in a graphite crucible (Shin-Nihon Techno Carbon Co., Ltd., IGS-743), which was placed inside a molded insulation material, and introduced into the chamber of a high-frequency induction heating furnace (Daiichi Kiden Co., Ltd., S08-5817) equipped with a high-frequency induction coil. The chamber was then heated for 10 minutes using a rotary pump and an oil diffusion pump. -3 The vacuum was drawn to the Pa range. Then, Ar gas (99.99%) was introduced to achieve atmospheric pressure, and heating was started with the furnace in an inert atmosphere (non-oxidizing atmosphere). First, the temperature was raised to 500°C over 30 minutes, and held at 500°C for 30 minutes. Then, the temperature was raised to 1400°C over 1 hour, and then held at 1400°C for 1 hour, and naturally cooled to room temperature. Then, impurities were removed in the same manner as in Example 1 to obtain a photocatalyst powder, and the photocatalyst powder was evaluated.
[0063] 4.Results The raw materials, synthesis conditions, and evaluation results of the photocatalyst powder for each of the examples and comparative examples are summarized in Table 1 below. In addition, the X-ray diffraction patterns of the photocatalyst powders for each of the examples and comparative examples are summarized in Figure 2. Furthermore, the particle size distribution measurement results of the photocatalyst powders for each of the examples and comparative examples are summarized in Figure 3.
[0064] [Table 1]
[0065] 5. Discussion The peak positions of the three strongest lines of 3C-SiC are 2θ=35.6°, 60.0°, and 71.8°. As shown in FIG. 2, the diffraction patterns of Examples 1-4 and Comparative Examples 1-3 show that the peak positions of the three strongest lines match, and the generation of 3C-SiC was confirmed. On the other hand, the diffraction patterns of Comparative Examples 4 and 5 show that the peak positions do not match those of 3C-SiC, and it is understood that 3C-SiC was not synthesized. The peaks of the X-ray diffraction patterns of Comparative Examples 4 and 5 match those of silicon (2θ=28°) and silicon dioxide (2θ=22°), and it is presumed that silicon remaining unreacted and silicon dioxide generated by reacting with oxygen in the furnace are present in the system. As described above, in this embodiment, it is understood that 3C-SiC is easily generated in the temperature range of 1400 to 1500°C. Although it is highly possible that 3C-SiC is produced at temperatures above 1500°C, this has not been confirmed due to the specifications of the furnace used (maximum temperature 1500°C). It is also believed possible to synthesize 3C-SiC at temperatures lower than 1400°C by adjusting the type of raw material and synthesis conditions. As far as the inventors have confirmed, 3C-SiC is particularly likely to be obtained when the heating temperature is between 1350°C and 1500°C.
[0066] As is clear from the results shown in Table 1, the 3C-SiC photocatalyst powders synthesized in an oxidizing atmosphere (Examples 1 to 4) all showed a significantly increased hydrogen production rate compared to the 3C-SiC photocatalyst powder synthesized in a non-oxidizing atmosphere (Comparative Example 1). In particular, a high hydrogen production rate was confirmed for the 3C-SiC photocatalyst powder synthesized in an oxidizing atmosphere at 1400°C.
[0067] Figure 4 shows the relationship between the specific surface area and the hydrogen generation rate, and Figure 5 shows the relationship between the pore volume and the hydrogen generation rate. In general, in the field of photocatalysis, it is known that the larger the specific surface area, the higher the water decomposition activity (hydrogen generation rate). However, as shown in Figure 4, in this example, even if the specific surface area of the 3C-SiC photocatalyst was increased, the hydrogen generation rate did not necessarily increase. On the other hand, when organized by the pore volume of the 3C-SiC photocatalyst as in Figure 5, a strong correlation with the hydrogen generation rate was confirmed.
[0068] In addition, in Example 4, the pore volume is larger than in Examples 2 and 3, but the hydrogen generation rate is low. This is presumably due to the difference in stacking fault density. It is generally known that crystal defects in photocatalysts become recombination sites of excited electrons and holes, reducing activity. From the X-ray diffraction pattern of each sample, the ratio x between the intensity at 2θ=33.6° and the intensity at 2θ=41.4° was taken, and the stacking fault density Y (%) of the 3C-SiC powder was calculated by substituting x into the following formula (Journal of the Ceramic Society of Japan 99 [6] 443-447).
[0069]
number
[0070] The stacking fault densities of Examples 2 to 4 were calculated by the above method, and the results were Y=4.24% for Example 2, Y=4.29% for Example 3, and Y=6.00% for Example 4. Therefore, it is considered that Example 4 had a higher stacking fault density than Examples 2 and 3, and exhibited a lower hydrogen evolution rate due to the greater number of recombination sites for excited electrons and holes.
[0071] Fig. 6 shows SEM images of the photocatalyst powders (partially) according to Examples 1 to 6 and Comparative Examples 1 to 3. In Comparative Example 1, 3C-SiC powder with exposed facets was synthesized, whereas in the other examples, 3C-SiC powder with no clearly exposed facets and with a complex dendritic shape was synthesized. It is believed that this difference in shape caused a large difference in the specific surface area and pore volume.
[0072] From the above results, it was found that when manufacturing 3C-SiC photocatalysts using the silicon carbonization method, a 3C-SiC photocatalyst with a large pore volume can be synthesized by setting the synthesis atmosphere to an oxidizing atmosphere. It was also found that 3C-SiC photocatalysts with a large pore volume have high water splitting activity and increase the hydrogen generation rate during water splitting. In particular, a significant increase in the hydrogen generation rate was confirmed in the sample synthesized at a low temperature of 1400°C. The cause of the increase in pore volume is unclear, but it is thought that the presence of oxygen causes some parts of the surface to oxidize and some parts to grow 3C-SiC during the synthesis process of 3C-SiC, resulting in the complex shape shown in Figure 5. [Explanation of symbols]
[0073] 11 Solar Simulator 12 Simulated sunlight 13 Mixture (water and photocatalyst) 14 Starla 15 Rubber stopper 16 Sealing material 17 Glass test tube 18 Stirring bar
Claims
1. 0.07 cm 3 / g or more of pore volume, It has a specific surface area of 0.5 m 2 / g or more and 50 m 2 / g or less, having a stacking fault density of 6% or less; 3C-SiC photocatalyst. However, the pore volume is measured by a gas adsorption method using a specific surface area / pore distribution measurement device, using a constant volume method with nitrogen as the adsorption gas, as follows. A glass tube containing a sample is immersed in liquid nitrogen at -196°C, and the inside of the tube is evacuated. Then, the relative pressure (=adsorption equilibrium pressure / saturated vapor pressure) is changed starting from 5.0 x 10 -4 and increasing by 2.5 x 10 -3 until it finally becomes 9.990 x 10 -1 , and the amount of adsorbed nitrogen is measured. From the measured amount of adsorbed nitrogen and the relative pressure, the pore distribution is calculated using the Dollimore-Heal (DH) method, which assumes that the pores are cylindrical, and the pore volume is obtained. The stacking fault density is measured from an X-ray diffraction pattern as follows: An X-ray diffraction pattern is obtained for a 3C-SiC photocatalyst using CuKα as a radiation source, and the ratio x between the intensity at 2θ=33.6° and the intensity at 2θ=41.4° is calculated, and the stacking fault density Y (%) is calculated by substituting this x into the following formula: [0010]
2. 0.10 cm 3 / g or more pore volume, The 3C-SiC photocatalyst according to claim 1.
3. Having an average particle size of 0.05 μm or more and 100 μm or less, 3C-SiC photocatalyst according to claim 1 or 2.
4. mixing a carbon source and silicon metal to obtain a mixture; and The mixture was heated in an oxidizing atmosphere to synthesize 3C-SiC, which was then heat-treated in air to remove carbon, and then treated with fluoronitric acid to remove metallic silicon and silicon dioxide, resulting in a 3C-SiC with a thickness of 0.07 cm. 3 to obtain a 3C-SiC photocatalyst having a pore volume of 0.5 m 2 / g or more, a specific surface area of 0.5 m 2 / g or more and 50 m 2 / g or less, and a stacking fault density of 6% or less; The method for producing a 3C-SiC photocatalyst includes the steps of: However, the pore volume is measured by a gas adsorption method using a specific surface area / pore distribution measurement device, using a constant volume method with nitrogen as the adsorption gas, as follows. A glass tube containing a sample is immersed in liquid nitrogen at -196°C, and the inside of the tube is evacuated. Then, starting from a relative pressure (=adsorption equilibrium pressure / saturated vapor pressure) of 5.0 x 10 -4 , the relative pressure is changed in increments of 2.5 x 10 -3 until it finally reaches 9.990 x 10 -1 , and the amount of adsorbed nitrogen is measured. From the measured amount of adsorbed nitrogen and relative pressure, the pore distribution is calculated using the Dollimore-Heal (DH) method, which assumes that the pores are cylindrical, and the pore volume is obtained. The stacking fault density is measured from an X-ray diffraction pattern as follows: An X-ray diffraction pattern is obtained for the 3C-SiC photocatalyst using CuKα as a radiation source, and the ratio x between the intensity at 2θ=33.6° and the intensity at 2θ=41.4° is calculated, and the stacking fault density Y (%) of the 3C-SiC photocatalyst is calculated by substituting this x into the following formula: [0025]
5. The temperature when the mixture is heated in an oxidizing atmosphere is 1350° C. or more and 1500° C. or less. The method according to claim 4.
6. The carbon source is carbon black.
6. The method according to claim 4 or 5.
7. The carbon black is at least one of thermal black and ketjen black. The method according to claim 6.
8. A method for producing hydrogen using the 3C-SiC photocatalyst according to any one of claims 1 to 3, comprising: producing hydrogen by irradiating the 3C-SiC photocatalyst with light while the 3C-SiC photocatalyst is in contact with water and decomposing the water. Hydrogen production methods.
9. A method for producing hydrogen using a 3C-SiC photocatalyst obtained by the method for producing a 3C-SiC photocatalyst according to any one of claims 4 to 7, comprising the steps of: bringing the 3C-SiC photocatalyst into contact with water, irradiating the 3C-SiC photocatalyst with light, and decomposing the water to produce hydrogen. Hydrogen production methods.
Citation Information
Patent Citations
Three-dimensional multistage structure nano silicon carbide, preparation method and application thereof
CN108285145A
Production of beta-type silicon carbide powder
JP1990059413A
Production of sic fine powder
JP1991054111A
Catalytic medium based on silicon carbide of high specific surface area in the form of granules with improved mechanical properties
JP2001507624A